Recent seismicity and slab gap beneath Toba caldera (Sumatra) revealed using hypocenter relocation methodology - Simanjuntak, Andrean (2024)
The Toba Lake is located in the northern part of Sumatra with a large complex caldera that formed by a supervolcano eruption 74,000 years ago and has been influenced by a tectonic process over several centuries. The tectonic process has produced recent seismicity in various systems, one of which is the Investigator Fracture Zone (IFZ). The IFZ incorporated with Sumatra subduction as a slab tear in the vertical direction beneath Toba. Therefore, we applied the hypocenter relocation method with a 1-D seismic velocity model to figure out the detailed structure beneath Toba and along the IFZ. The results show a significant change in hypocenter quality which is around 90% of total hypocenters with RMS < 1.0s, while 60% of total hypocenters have RMS < 0.5s following an oblique angle of ~65° beneath Toba. The results strongly highlight a slab gap of Sumatra subduction that may construct a slab tear with a gap at a depth > 100 km, and indicate a shallower dip to the northwest of Toba. A possible slab tear with a slab gap can be found along IFZ as the consequence of a rheologically weak structure which varies from the north to the south.